Using ICT as a platform for effective Information services delivery in information age: Kenneth Dike Library, University of Ibadan experience (2016)
Teaching, Learning and Research (TLR) initiatives in the institutions of higher learning, particularly in the University systems in the Information Age, are driven by digital data. Academic Libraries worldwide are emerging as critical partners in the creation, access, use, and preservation of (TLR) data. Digital stewardship, infrastructural development, economic models, and policies required to administer and protect TLR data, present both new opportunities and challenges for 21st century libraries. Addressed in this write-up are documentations of some of the things that Kenneth Dike Library, University of Ibadan, Ibadan, Nigeria has achieved, using Information and Communications Technology(ICT) as a platform to enhance an efficient and a robust information services delivery in pursuant of TLR initiative of the University of Ibadan.